These Factors associated with intrafamily violence in pregnant women in a Peruvian mother-child center.: Factores asociados a violencia intrafamiliar en gestantes de un centro materno infantil en Perú. - Bejarano, Gretty (2024)
Introduction: Domestic violence in pregnant women is considered a serious public health problem that affects the well-being of the mother and child. Objective: To determine the factors associated with intrafamily violence in pregnant women at the Tablada de Lurín Maternal and Child Center during the period 2021-2022. Methods: Analytical cross-sectional study. The clinical histories of a first level health center were used. The main variable was domestic violence; the independent variables were demographic and social characteristics, number of children and previous illness. Results: Domestic violence occurred in 15.63%. In the first simple regression analysis, it was found that pregnant women with more than 4 children, with a confidence interval of 2.44, presented a higher frequency of suffering intrafamily violence compared to pregnant women who had less than or equal to 2 children. In the second multiple regression analysis, it was observed that pregnant women with more than 4 children presented a higher frequency of suffering intrafamily violence compared to pregnant women who had less than or equal to 2 children. Conclusions: It was found that pregnant women who suffered family violence represented 15.6%. Pregnant women with more than 4 children were 239% more likely to suffer domestic violence than women with fewer than 2 children, regardless of maternal age, being married or single, having higher education or having a previous illness.